Personal Interest or Beneft – A Need of A Contemporary Man - Milošević Šošo, Biljana Č. (Sociološki pregled, 2018)
The aim of this paper is to point to the ever prominent and increasingly present warped need that has appeared, or better to say, that has developed in the modern man due to the existing social circumstances. The category of personal interest or beneft can be classifed under one of the many ethical issues of modern time, which again carries a series of contradictions in itself in the context of social processes. The author is also in a dilemma on whether it is desirable to write about this problem today, because personal interest and self-interest, according to Marshall Sahlins, as the worst in us, has become something that is best during the twentieth century. The paper will present the results from a part of empirical research which provides insight into the motives of making connections with other people in the Republic of Srpska.